The trouble with twin studies - Joseph, Jay. (NEW YORK ROUTLEDGE, 2015)
"The Trouble with Twin Studies questions popular genetic explanations of human behavioral differences based upon the existing body of twin research. Psychologist Jay Joseph outlines the fallacies of twin studies in the context of the ongoing decades-long failure to discover genes for human behavioral differences, including IQ, personality, and the major psychiatric disorders. This volume critically examines twin research, with a special emphasis on reared-apart twin studies, and incorporates new and updated perspectives, analyses, arguments, and evidence. "--
Keywords: Twins; Twins; PSYCHOLOGY / General; PSYCHOLOGY / Personality